A comparative study of the effect of bacteria and yeasts communities on inoculated and spontaneously fermented apple cider. (May 2023) - Han, Yingying; Du, Jinhua
Abstract: Understanding bacteria and yeasts communities can reduce unpredictable changes of apple cider. In this study, apple juice inoculated with Saccharomyces cerevisiae WET 136 and fermented spontaneously were compared, the relationships of bacteria, yeasts, organic acids, and volatiles were analyzed. Results showed that microbial diversity affected the fermentation, organic acids and volatiles in apple ciders. In the first four spontaneous fermentation days, LAB (lactic acid bacteria) multiplied and reached 7.89 lg CFU/mL, and then triggered malolactic fermentation (MLF), leading to malic acid decreased by 3880.52 mg/L and lactic acid increased by 4787.55 mg/L. The citric, succinic and fumaric acids content was 2171.14, 701.51 and 8.06 mg/L lower than that in inoculated cider, respectively. Although the yeasts multiplied during spontaneous fermentation, it did not reach 7.50 lg CFU/mL until the 5th day, which led to a long lag period, as well as later and lower production of acetaldehyde and higher alcohols. The inoculated yeast inhibited LAB, acetic acid bacteria, Rahnella, and non- Saccharomyces . Yeasts were the key to produce citric acid, acetaldehyde and 3-methyl-1-butanol in apple cider; while bacteria were closely related to the formation of lactic acid, acetic acid and ethyl acetate. It suggested that low higher alcohols and acetaldehyde can be realized by selecting yeasts, and Leuconostoc pseudomesenteroides can work as candidate to reduce L-malic and citric acids in apple cider. Highlights: Leuconostoc pseudomesenteroides trigger MLF in spontaneous fermentation. Bacteria were positively related to lactic acid, acetic acid, ethyl acetate, and 1, 2-propanediol. Bacteria inhibited the formation of citric acid, acetaldehyde and 3-methyl-1-butanol. Bacterial diversities in inoculated cider were higher than that in spontaneous cider. Inoculated yeast inhibited LAB, acetic acid bacteria and non- Saccharomyces.